EVIDENCE AND MANIFESTATIONS OF VOLCANIC ACTIVITY ON MERCURY - Vidmachenko, Anatoliy (Collection of scientific papers «ΛΌГOΣ», 2025)
The earliest hints of volcanic activity on Mercury came from observations by the “Mariner 10” mission. And the results of the “MESSENGER” mission provided compelling evidence that volcanism on Mercury played a key role in shaping the planet's surface. Numerous landforms characteristic of volcanic activity has also been identified on Mercury. Evidence of effusive volcanism with lava flows is represented by large smooth plains that can be interpreted as solidified flows of basaltic lava that poured onto the surface. The blade-shaped edges of many lava flows are clearly visible, lava channels and a large shield volcano have been found. Evidence of possible volcanism is evidence of its explosive activity. The age of Mercury's lava surfaces shows that large-scale effusive volcanism ceased about 3.5 billion years ago due to planetary cooling. Then Mercury's crust entered a state of global compression. The discovery of widespread pyroclastic vents and deposits on Mercury has important implications for the volatile content of the planet's bulk and its thermal evolution. The presence of volatile elements, and especially sulfur, is considered a key factor that could contribute to the presence of explosive volcanism on Mercury. The most extensive manifestation of effusive volcanism on Mercury is the formation of smooth plains of large sizes. That is, powerful massive outpourings of relatively liquid lava on Mercury covered vast areas. The geological history of Mercury is the result of a complex interaction between its internal thermal evolution, volcanism processes, and tectonic deformations caused by the global compression of the planet. Mercury's huge core would have played a central role in all of these processes.